The Existence of Islamic Religious Counselors in Combating Underage Marriages in Mandalle Sub-district - Saripuddin; Agus Muchsin; Rahmawati; Rusdaya Basri; Zainal Said (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
Underage marriage is a marriage at a young age. The government has set the ideal marriage age at 19 for both parties. However, there are still cases of marriages below the age of 19. The purpose of this research is to identify the factors causing underage marriages in Mandalle Sub-district. This research is a qualitative study with a case study approach. Data collection techniques include observation, interviews, and documentation. The research design is descriptive. The results show that, first, the factors causing underage marriages in the Office of Religious Affairs (KUA) in Mandalle Sub-district, Pangkajene, and Kepulauan Regency are due to low education, lack of knowledge about marriage laws (Law No. 16 of 2019), economic factors, cultural factors, and unwanted pregnancies. Second, the efforts made by Islamic religious counselors in KUA Mandalle Sub-district, Pangkajene, and Kepulauan Regency in handling underage marriages are: (a) conducting counseling or socialization to the community, especially teenagers; (b) Providing information about the impact of underage marriages; (c) Emphasizing the role of parents, as parents play a significant role in a child's decision to marry early. Parents are expected to provide insights and full control over their children so that they understand the consequences of underage marriages.